Approach to Management of Cardiac Calcified Amorphous Tumor - Wilson, Parker; Pillai, Priyamvada; Reiss, Jacob; Zhou, Matthew; Rafael, Aldo; Mody, Purav (The American journal of cardiology, 2025)
A 76-year-old female with a known medical history of treated essential hypertension, hyperlipidemia, and obesity presented to her primary care provider for 2 months of worsening left-sided vision loss. Ophthalmologic evaluation demonstrated a left retinal artery branch occlusion leading to echocardiographic evaluation which revealed a large mobile echodensity on the mitral valve. Given specific clinical features and echocardiographic characteristics, the suspicion was highest for calcified amorphous tumor (CAT). Excision of this mass confirmed the diagnosis of CAT. There is currently clinical equipoise in literature regarding the best treatment strategy for these tumors therefore a multidisciplinary approach should be used to formulate individualized treatment plans.